PENGARUH LABA AKUNTANSI, EARNING PER SHARE (EPS) DAN LABA TUNAI TERHADAP DIVIDEN KAS (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Wiwin Leony Bidari; Putu Kepramareni; Ni Luh Gde Novitasari (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
The manufacture dividend’s policy is very important for the investors. Those because the company’sprofits will be used more to pay dividend than retained earnings or vice versa. In caseof dividend’s policy, the most concerned factor by management is the amount of profit that earnsby the company, such as accounting earnings, Earning Per Share (EPS), and cash income.This study aimed to know the effect of accounting earnings, earning per share (EPS), and cashincome to cash dividend in Indonesia Stock Exchange (BEI). Sample selected using PurposiveSampling Method, with total sample 37 companies that registered in Indonesia Stock Exchangeon period year 2014 to 2016. Multiple linear regression analysis used to test the hypothesis.The results show that accounting earnings and earning per share (EPS) have no effect to cashdividend, but cash income have positive determination to cash dividend in manufacture companiesthat registered in Indonesia Stock Exchange (BEI) year period 2014 – 2016.